Response of the Kebon Jambu Islamic Boarding School to the Framing of the Television Broadcast of the Xpose Uncensored Trans7 Program: A Case Study of the October 13, 2025 Broadcast - Muhammad Dzulfikar; Farida Nurfalah; Novicky Alban Adiputra (Jurnal Polisci, 2026)
Background. Television media has a strategic role in shaping social reality through the framing process, including in representing religious institutions such as Islamic boarding schools. The October 13, 2025 edition of Xpose Uncensored Trans7 showcases pesantren through narratives and visuals that cause controversy and influence public perception. Aims. This study aims to analyze the framing of pesantren in the Xpose Uncensored Trans7 show and examine the response of the Kebon Jambu Islamic Boarding School to the framing. This study uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with caregivers, managers, and students of the Kebon Jambu Islamic Boarding School, as well as through documentary documentation and supporting literature. Data analysis was carried out using Robert N. Entman's framing theory. Results. The results of the study show that the Xpose Uncensored Trans7 show frames pesantren reducively and tends to ignore the context of pesantren values, traditions, and educational relationships. The response of the Kebon Jambu Islamic Boarding School shows a critical and reflective attitude through the rejection of media stigma and efforts to maintain the cultural identity of the Islamic boarding school. Conclusion. This study concludes that pesantren play an active role in responding to media construction, thus emphasizing the importance of journalistic practices that are contextual and sensitive to cultural values.